Dysleksi: Tidlige risikomarkører for dysleksi - Riise, Sølvi Grønning (UiT Norges arktiske universitet, 2021)
The purpose of this master's thesis was to investigate whether or not students who were identified with poor literacy skills at 3rd grade, displayed poor literacy skills at the start of 1st grade and in 2nd grade. The theoretical framework for the master's thesis is the prevailing etiological model for dyslexia, namely the Multiple Deficit Model (MDM). It suggests that dyslexia (and other developmental disorders) are multifactorial, and that several genetic risk factors interact with each other and with several environmental risk factors resulting in disorders on the behavioral level. The analyzes in the master's thesis are based on longitudinal data from the Tromsø Longitudinal Study of Dyslexia (TLD), which has followed a cohort of children over several years, and their parents. The children were grouped according to scores above or below 20th percentile on a reading test in the 3rd grade. The groups were compared on letter knowledge, phonological awareness, rapid naming and working memory in 1st and 2nd grade. The results showed that phoneme isolation, rapid naming and working memory are cognitive risk markers for poor reading skills, and that the difficulties are present even before school entry and before the start of formal reading and writing training. The percentage of children with reading difficulties who also had parents with writing difficulties, were higher than for the children wo did not. These findings have important implications for preventive work and early intervention in kindergarten and school. Sammendrag Hensikten med denne masteroppgaven var å undersøke om elever som ble identifisert med svake skriftspråkferdigheter på 3. trinn, også hadde vansker med skriftspråkrelaterte ferdigheter på henholdsvis 1. og 2. trinn. Den teoretiske rammen for masteroppgaven er den rådende etiologiske modellen for dysleksi, nemlig «flervanske-modellen» eller Multiple Deficit Model (MDM). Den foreslår at dysleksi (og andre utviklingsforstyrrelser) er multifaktoriell, og at flere genetiske risikovarianter ...